Effects of sintering on the microstructure and electrical properties of ZnO-based thermoelectric materials. (15th October 2017) - Tian, Tian; Cheng, Lihong; Xing, Juanjuan; Zheng, Liaoying; Man, Zhenyong; Hu, Dongli; Bernik, Slavko; Zeng, Jiangtao; Yang, Jia; Liu, Yi; Li, Guorong
Highlights: The reducing-atmosphere sintering (N2  + CO) method leads to the highest power factor for ZnO-based thermoelectric materials. The spark plasma sintering (SPS) method leads to the highest conductivity for the ZnO ceramics. Both the SPS and the reducing-atmosphere sintering methods eliminated the intrinsic acceptor defects at the grain-boundaries. The SPS method can increase the solubility of Ti for ZnO ceramics, which increased the carrier concentration. Graphical abstract: Abstract: Both the spark plasma sintering (SPS) method and reducing atmosphere sintering (N2  + CO) method could greatly improve the electrical performance of ZnO-based thermoelectric materials. However, there is no comparison of these two methods which is essential for further improvements to the thermoelectric performance. In this article, a systematic comparison of the microstructures and electrical properties of the ZnO-based thermoelectric materials prepared by the SPS method, the reducing atmosphere sintering (N2  + CO) method, and the conventional sintering method was presented. The ZnO-based thermoelectric materials prepared by the reducing atmosphere sintering (N2  + CO) method showed the highest power factor with a moderate carrier concentration and a high Hall mobility, while the sample prepared by the SPS method exhibited the highest electrical conductivity of 2.3 × 10 5  S·m − 1 with a lower power factor. The ultra-high electrical conductivity of the SPS processed sample was mainly due to the increased solubility of Ti, which led to a higher carrier concentration. Moreover, the grain-boundary structure, which is important for the electrical performance, was also systematically analyzed by EBSD and CL. It can be concluded that the reducing atmosphere sintering (N2  + CO) method is more suitable for thermoelectric applications, while the SPS method is an effective way to produce highly conductive ZnO ceramics.